PSYCHOLOGICAL WORK WITH CONVICTED PERSONS: PSYCHOTHERAPY OR PSYCHOLOGICAL COUNSULTATION? - Черехович, Максим (State and Law, 2021)
The psychological work that exists in modern correctional institutions is carried out mainly in the form of psychological counseling, which is often not able to ensure the fulfillment of the tasks of the psychological service to provide a corrective effect on the personality of the convicted person, his behavior and further resocialization. The author tried to reveal the difference between psychotherapeutic and psychological counseling work, showing that in addition to the actual psychological counseling in working with convicts, psychotherapeutic activity is necessary and, consequently, the presence of a psychotherapist on the staff of a correctional institution.
Keywords: convict's personality, psychological work, psychotherapy, correction, resocialization